Talak dan iddah bagi Wanita dalam perspektif islam - 29, diah kumala (Maliki Interdisciplinary Journal, 2026)
This article explains about talak and iddah from an Islamic perspective, the provisions of iddah, and how talak occurs in certain circumstances. Iddah is a waiting period for women after being divorced or left by their husband, while talak is a word of divorce given by the spouse to the spouse which results in the severing of the marriage bond. In terms of divorce, there are 2 types, namely; (1) Talak raj’i, and (2) Talak Ba’in Sughra and Kubra. The iddah period for women is detailed Nash, which includes; (1) if a woman’s whose husband passes away, her iddah is 4 months and 10 days, (2)if a wife who is divorced during her pregnancy, her iddah continues until she delivers, (3) Women who have exprerienced menupause are typically 50 years or older. At that age, a woman’s blood usually stops, and she is required to perform iddah if her husband divorces her or dies.